Respuesta :

Hello!

You could write this equation as seen below.

6+2(x+4)=0.5(3-x)

I hope this helps!

Answer:

The required equation is [tex]6+2(x+4)=\frac{1}{2}(3-x)[/tex].

Step-by-step explanation:

Let x be the unknown number.

We have to find the equation for the statement “six added to twice the sum of a number and four is equal to one-half of the difference of three and the number”.

Twice the sum of a number and four = 2(x+4)

Six added to twice the sum of a number and four is equal = 6+2(x+4)

Difference of three and the number = (3-x)

One-half of the difference of three and the number = [tex]\frac{1}{2}(3-x)[/tex].

Since six added to twice the sum of a number and four is equal to one-half of the difference of three and the number, therefore

[tex]6+2(x+4)=\frac{1}{2}(3-x)[/tex]

Hence, the required equation is [tex]6+2(x+4)=\frac{1}{2}(3-x)[/tex].